Putting invertebrates on the agenda: political and beaurocratic challenges. - Majer, Jonathan; Horwitz, P.; Recher, H. F. (1999)
The Invertebrate agenda can be characterized by a series of inter-related laments: not enough funds; poor taxonomic understanding; too few scientists dealing with too many taxa; dominant detracting notions like cute and cuddly; and that vertebrates and/or vegetation communities are assumed to be adequate surrogates for conservation planning. These laments have not diminished in recent years, despite the release of the National Strategy for the Conservation of Australia's Biological Diversity. Our analysis suggests that the Strategy's commitments to taxonomic knowledge, and raising understanding and awareness ofinvertebrates, have not yet borne fruit, and there remains an over-emphasIs on vertebrates, flowering plants, threatened taxa and threatened processes, and an under-emphasis on the importance of invertebrates in ecosystem functioning.